Air Passivation of Chalcogen Vacancies in Two‐Dimensional Semiconductors. Issue 3 (24th November 2015) - Liu, Yuanyue; Stradins, Pauls; Wei, Su‐Huai
Abstract: Defects play important roles in semiconductors (SCs). Unlike those in bulk SCs, defects in two‐dimensional (2D) SCs are exposed to the surrounding environment, which can potentially modify their properties/functions. Air is a common environment, yet its impact on the defects in 2D SCs still remains elusive. Here we study the interaction between air and chalcogen vacancies (VX ), the most typical defects in 2D SCs. Although the interaction is weak for most molecules in air, O2 can be chemisorbed at VX with a barrier that correlates with the SC cohesive energy and can be overcome even at room temperature for certain SCs. Importantly, the chemisorbed O2 changes the VX from commonly believed harmful carrier‐traps to electronically benign sites. This unusual behavior originates from the isovalence between O2 and X when bonded with metal. Based on these findings, a facile approach is proposed to improve the performance of 2D SCs by using air/O2 to passivate the defects. Abstract : The interaction between air and chalcogen vacancies (VX ), the most typical defects in 2D semiconductors (SCs), is calculated. The chemisorbed O2 changes the VX from commonly believed harmful carrier‐traps to electronically benign sites. This unusual behavior originates from the isovalence between O2 and X when bonded with metal. A facile approach is proposed from this to improve the performance of 2D SCs by using air/O2 to passivate the defects.